Moral Defenses in the Poetry of Tramps(Alsa’alik) - د. رحيق صالح فنجان (Thi Qar Arts Journal, 2021)
The tramps (Alsa’alik) represent the untouchable class in the pre-Islamic society. They are either individuals who were ousted by their tribes for a crime they committed and then absolved themselves of them, or strangers who were ostracized and enslaved for the blackness of their color, or the poor who were tired of the unjust division of wealth, and sought for the poor to have a share of it instead of monopolizing it by the rich. So they cut their relations with their tribes, preferring the desert and its beasts when they chose the task of equitable distribution of wealth among the tramps as they were plundering it from the rich. Living in the desert amidst beasts, demanding opponents, and scarce supplies and people in addition to what is known are swords, spears, and arrows, is not enough to be financially armed of the tramp rather it requires additional armament represented by moral means: courage, endurance, persistence, rebellion against humiliation and slavery, caution and resourcefulness, and contempt for death.